Efficacy and safety of combined stent retriever and contact aspiration vs. stent retriever alone on revascularization in patients with acute ischemic stroke: a systematic review and meta-analysis - Li, Wei; Lin, Guo-hui; Li, Hong-hong; Zhou, Peng-bo; Chen, Yue-yang; Sun, Hong-tao; Chen, He-cheng (Frontiers in Neurology, 2024)
Objective Whether the efficacy of combined stent retriever and contact aspiration (S + A) is superior to stent retriever (S) alone for revascularisation in patients with large vessel occlusive stroke remains uncertain. The aim of this meta-analysis was to assess the safety and efficacy of combined stent retriever and contact aspiration for the treatment of acute ischaemic stroke with large vessel occlusion by comparing it with stent retriever alone. Methods We systematically searched the PubMed, Embase, Web of Science, and The Cochrane Library databases for randomised controlled trials and observational studies (case-control and cohort studies) published before 1 October 2023 comparing the efficacy of combined stent retriever and contact aspiration versus tent retriever alone in patients with large vessel occlusive stroke. The end point of the primary efficacy observed in this meta-analysis study was the rate of first pass nearly complete or complete recanalisation (mTICI 2c-3). Secondary effectiveness nodes were: rate of first pass successful recanalisation (mTICI 2b-3), rate of near-complete or complete recanalisation of the postoperative vessel, rate of successful recanalisation of the postoperative vessel, and MRS 0–2 within 90 days. Safety endpoints were interoperative embolism, symptomatic intracranial haemorrhage, and mortality within 90 days. Results A total of 16 studies were included in the literature for this meta-analysis, with a total of 7,320 patients (S + C group: 3,406, S group: 3,914). A comprehensive analysis of the included literature showed that combined stent retriever and contact aspiration had a higher rate of near-complete or complete recanalisation of the postoperative vessel [OR = 1.53, 95% CI (1.24, 1.88), p < 0.0001] and rate of successful recanalisation of the postoperative vessel compared to stent retriever alone [OR = 1.83, 95% CI (1.55, 2.17), p < 0.00001]; there were no statistically significant differences between the two groups in terms of the rate of first pass nearly complete or complete recanalisation [OR = 1.00, 95% CI (0.83, 1.19), p = 0.96], rate of first pass successful recanalisation [OR = 1.02, 95% CI (0.85, 1.24), p = 0.81], interoperative embolism [OR = 0.93, 95% CI (0.72, 1.20), p = 0.56], symptomatic intracranial haemorrhage [OR = 1.14, 95% CI (0.87, 1.48), p = 0.33], MRS 0–2 within 90 days [OR = 0.89, 95% CI (0.76, 1.04), p = 0.14] and mortality within 90 days [OR = 1.11, 95% CI (0.94, 1.31), p = 0.22]. Conclusion Combined stent retriever and contact aspiration has a higher rate of postprocedural revascularisation (mTICI 2c-3/mTICI 2b-3) compared with stent retriever alone in patients with large vessel occlusion stroke. In addition, it was not superior to stenting alone in terms of the rate of first pass recanalisation (mTICI 2c-3/mTICI 2b-3), interoperative embolisation, symptomatic intracranial haemorrhage, good functional prognosis within 90 days and mortality within 90 days.